The manufacture of medium density fibreboard from rubberwood of different age groups - Mohd Nor M Y (Journal of Tropical Forest Products, 1995)
Rubberwood [Hevea brasiliensis] from 3-, 8- and 14-year-old trees was found to have a mean wood density of 530, 540 and 530 kg m-3, respectively, with a corresponding fibre length of 1.24, 1.33 and 1.40 mm. Medium density fibreboard (MDF) with a density of about 700 kg m-3 manufactured from rubberwood of age groups 3, 8 and 14 years satisfied the requirements of type 300 of the standard JIS A 5906-1983, i.e. the bending strength and the internal bond of all the boards exceeded the 300 kg cm-2 and 5.0 kg cm-2, respectively. However, MDF from 3- and 8-year-old rubberwood had higher internal bond strength (IB) than that of 14-year-old rubberwood.
Source Year: 1996